THE EFFECTIVENESS OF MAKE A MATCH TECHNIQUE IN TEACHING VOCABULARY (ELang | An English Language Education Journal, 2023)
The title of this research paper is “The Effectiveness of Make A Match Technique in Teaching Vocabulary. This research aimed to answer two research problems. 1). Is the use of make a match technique effective to improve students’ vocabulary in first grade of junior high school Nur Muhammad? 2). To find out the students’ response toward the use make a match technique in improving vocabulary in first grade of junior high school Nur Muhammad? To know whether this technique effective or not, the writer used pre-experimental research applied in VII-B class. The study had been done in four meetings that were designed; first meeting was for pre-test, 2 meetings were for treatments, and the last meeting was for post-test. As the quantitative method, the writer analyzed the data by using t-test by pretest, posttest and questionnaire. Based on the two research problems above, the researcher found that the result showed that there was significant difference on the students’ vocabulary achievement taught with Make A Match. The students’ mean of pre-test’s score of experiment class was 42.5. Then in post-test, the mean score of experiment class was 73.5. The df 19, t-table at the level of significance of 0.5 for two tailed is 2.093 as to is bigger than t-table (15.21 > 2.093). In other words, make a match technique is effective in teaching vocabulay for the first grade of junior high school students. The questionnaire data showed that most the students like learning English and interested in learning vocabulary. Students' vocabulary also increased after using make a match technique. In other words, the students’ gave positive response toward the use of make a match. This result hopefully would motivate language teacher to use make a match in teaching English in the classroom